Model data flow and collection from VDR for close-quarter situational analyses and collision avoidance - Dandu Basappa, Rithvik (My University, 2022)
The current leap in digitalization in the maritime industry is propelling the research and development of many new technologies to assist in the decision-making process for the navigator in close-quarter situations (CQS) for effective collision avoidance. The Voyage Data Recorder (VDR) onboard vessels records and stores various information from different sensors available such as position, speed, course, etc., In the case of maritime casualty, the data collected by VDR can be retrieved for investigation purposes. According to the new amendments to the VDR regulations, the recorded data can be played in real-time using playback equipment. The VDR data if available continuously and extracted easily, can enhance the research work to develop collision avoidance technologies in CQS that can be used for autonomous shipping in the future. Many scientific articles have been published about methodologies used for collision avoidance using advanced programming techniques and different variables that are required which could be available in the VDR data. This master thesis researches different variables, its source sensors, and data interfaces that are available in the VDR. Moreover, it also explores the international regulations and standards used for recording the data and its interfaces. Additionally, this research also explores different methodologies proposed by researchers and identifies the variables that were used in collision avoidance and for CQS analyses. Another outcome of this thesis is the development of a simple conceptual model for data flow parameters relationship showing various variables available in the VDR data and their source sensors which can be extracted and used Collision Alert System (CAS) for CQS.
Keywords: Voyage data recorder; close-quarter situation; navigational sensor; autonomous navigation; collision avoidance; collision risk assessment; data interface; performance standards; playback equipment; automatic radar plotting aids; IMO; NMEA; IEC; Maritime Management